Analysis of Coherence and Cohesion in Narrative Paragraphs of SMAN 4 Singaraja XI Grade Students - Putu Ayu Yulia Angelina Putri; Ni Luh Putu Sri Adnyani; Dewa Putu Ramendra Ramendra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This research aimed to analyze exposure related to the coherence and cohesiveness of paragraph texts of SMAN 4 Singaraja students in the 2024/2025 academic year, especially in class XI K. The research method used was mixed method consisting of qualitative and quantitative descriptive methods. The quantitative descriptive method was used to answer the first objective, and the qualitative descriptive method was used to achieve the second objective. Data were collected through document collection, namely narrative text assignments. Furthermore, the data were analyzed descriptively. In general, the study showed that the average coherence level of students' narrative writing reached 77.13%, which was categorized as ‘good’. This means that most students were able to convey the topic quite clearly and relevantly, using appropriate supporting details, and well-organized purpose and structure. However, topic development was still not maximized and the flow between sentences was sometimes not smooth. In cohesion device, students generally showed use of cohesion, especially lexical cohesion which reached around 60%, as well as conjunctions and references which reached 20% each. Keywords: Coherence, Cohesion, Narrative Paragraph